Uji Performansi Getaran Mekanis dan Kebisingan Mist Blower Yanmar MK 150-B - Ahmad Noval Irvani; Mad Yamin (PERTETA, 2012)
Abstract Mist blower is one of the mechanization tool of agriculture considered as a tool that can assist humans in fertilizer and pesticides spreading activities. Levels of motor speed in the used mist blower were 1915, 4009, and 7227 rpm. Vibration measurements were conducted on the engine and handlebar control mist blower with the three-dimensional axes namely X, Y, and Z. Mist blower noise measurements were performed on the engine, operator's right ear and left ear. Based on the analysis of vibration and noise from the mist blower of type MK 150-B was obtained the safe limit values from the use of these tools. The safe limit of the use of mist blower in motor rotation speed of 1915, 4009, and 7227 rpm after being compared with the vibration and noise were 1 hour, 1 hour and 24 minutes respectively. The farther the distance from noise source, the lower the noise level too. Moreover objectivity study of operator was conducted. The first farmer was tired faster than the second farmer. In terms of age of farmer, the second farmer (60 years) older than the first farmers (40 years), but this should not affect significantly. Activity on the previous day greatly affects the level of fatigue when operating the mist blower. This was because the first farmers did more activities and had rest periods that less than second farmer. Keyword: mist blower, vibration, noise